Caste- and environment-associated differential expression of olfactory receptors in pest ants - Kayli R. Sieber; Maya Saar; Nicholas Newell; Katrina Fernandez; Flávia P. Franco; Fernando R. Sujimoto; Charlotte B. Francoeur; Roberto M. Pereira; Cameron R. Currie; José Mauricio Simões Bento; Hua Yan (Scientific Reports)
Abstract As human society continues to grow and evolve, so does the need for effective pest management strategies. Olfactory-mediated control methods, such as attractant and repellent compounds, are a proposed strategy for mitigating the damaging effects of some insect pests, most notably ants, that rely on olfaction for communication. To develop such compounds, it is first important to comprehensively understand the target species’ olfactory transcriptome in order to guide future targeted functional characterization of relevant olfactory proteins. Here, we perform bulk RNA-seq analysis of antennae from three notable pest ant species, Camponotus floridanus, Atta sexdens, and Atta cephalotes. Specifically, we highlight the expression profiles of olfactory receptor genes, as they may serve as potential targets of future industry research and application. We find that the ant antennal transcriptome differs between each species’ castes, potentially reflecting varying behaviors and tasks, and also appears to be influenced by the surrounding environment. Our findings suggest a general up-regulation of olfactory receptor genes amongst foraging castes, also demonstrating that, when comparing foraging ants from differing environments, olfactory-related genes exhibit considerable patterns of differential expression. These findings suggest variable olfactory sensitivity depending on the aforementioned factors, warranting further investigation into whether differing caste and environmental conditions may negatively influence the effectiveness of broad-range olfactory-mediated pest management strategies. Development of pest management tools that target specific groups of insects by environment or caste may lead to more effective control.